Subjective Benefits of Bimodal Listening in Cochlear Implant Recipients with Asymmetric Hearing Loss. (17th March 2020) - Thompson, Nicholas J.; Dillon, Margaret T.; Buss, Emily; Rooth, Meredith A.; King, English R.; Bucker, Andrea L.; McCarthy, Sarah A.; Deres, Ellen J.; O'Connell, Brendan P.; Pillsbury, Harold C.; Brown, Kevin D.
Abstract : Objective: To investigate the influence of cochlear implant (CI) use on subjective benefits in quality of life in cases of asymmetric hearing loss (AHL). Study Design: Prospective clinical trial. Setting: Tertiary academic center. Subjects and Methods: Subjects included CI recipients with AHL (n = 20), defined as moderate‐to‐profound hearing loss in the affected ear and mild‐to‐moderate hearing loss in the contralateral ear. Quality of life was assessed with the Speech, Spatial, and Qualities of Hearing Scale (SSQ) pragmatic subscales, which assess binaural benefits. Subjective benefit on the pragmatic subscales was compared to word recognition in quiet and spatial hearing abilities (ie, masked sentence recognition and localization). Results: Subjects demonstrated an early, significant improvement ( P <. 01) in abilities with the CI as compared to preoperative abilities on the SSQ pragmatic subscales by the 1‐month interval. Perceived abilities were either maintained or continued to improve over the study period. There were no significant correlations between results on the Speech in Quiet subscale and word recognition in quiet, the Speech in Speech Contexts subscale and masked sentence recognition, or the Localization subscale and sound field localization. Conclusions: CI recipients with AHL report a significant improvement in quality of life as measured by the SSQ pragmatic subscales over preoperative abilities. Reported improvements are observed as early as 1 month postactivation, which likely reflect the binaural benefits of listening with bimodal stimulation (CI and contralateral hearing aid). The SSQ pragmatic subscales may provide a more in‐depth insight into CI recipient experience as compared to behavioral sound field measures alone.